Penerapan Manajemen Risiko Berbasis Aset Sebagai Salah Satu Bentuk Pengamanan Perusahaan pada PT.XYZ - Wira Yudha Nuswantoro; Yekti Condro Winursito (MAMEN: Jurnal Manajemen, 2023)
In today's globalized era, a company's competitiveness is largely determined by its environment, both the internal environment and the external environment. The competition certainly involves various assets. Company PT. XYZ is a large company engaged in the procurement of goods in East Java Province, as a large company, of course, it will pay close attention to the assets it owns. Security handling of assets is closely related to the various risks faced. Therefore, the security of these assets is included in risk management. The purpose of this research is to find out how the implementation of asset-based risk management in PT. XYZ. The method used in this study is a literature study which will later be compared with the results obtained. This study also uses a qualitative approach that aims to understand the implementation of risk management at PT. XYZ. The results of this study are the application of risk management that has been carried out by PT. XYZ is going well. The existence of standard SOPs/procedures that already exist and regular evaluations/reviews can minimize the occurrence of risks in business processes that will occur in the future.